Study of Hypermetropia in a Senegalese Hospital - AS Sow; EA BA; M Nguer; H Kane; JM Ndiaye; AM KA; JP Diagne; ME Demeideros; AM Wane; PA Ndoye Roth; PA Ndiaye; MR Ndiaye (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2018)
The cases of hypermetropia in patients aged 5 to 40 years were studied at Aristide Le Dantec hospital in Dakar. There are 85 patients including 28 men and 57 women. The average age was 22 years old. Headache was the most common reason for consultation (79.69%). The average consultation time was 6 days after onset of functional symptoms. Complications were strabismus (21.88%) and amblyopia (3.12%). A negative impact on the socio-professional level was noted in 60.94%. The treatment consisted of an optical correction by glasses in 96.87%.